Brief History and Description of Some Sports - Ochilov Rufat Kukanovich (Zien Journals, 2023)
The first modern Olympic Games were held in Athens on April 6, 1896. This date is the beginning of the history of modern games. Then they were called the First International Olympic Games. The Olympic Games are one of the most important international sports events that unite all people through sports. The games are held every 4 years and serve as a great reality for all mankind.
Keywords: Olympic Games; International Olympic Committee; historical sports